Standardisation of canine meningioma grading: Inter‐observer agreement and recommendations for reproducible histopathologic criteria. (3rd February 2022) - Belluco, Sara; Marano, Giuseppe; Baiker, Kerstin; Beineke, Andreas; Oevermann, Anna; Seehusen, Frauke; Boracchi, Patrizia; Pumarola, Marti; Mandara, Maria Teresa
Abstract: The human grading system is currently applied to canine meningioma, although it has not been validated in dogs. The present study focused on standardising the human grading system applied to canine meningioma. Four veterinary neuropathologists graded 186 canine meningiomas as follows: Grade I tumour, with <4 mitoses/2.37 mm 2 ; Grade II tumour, with ≥4 mitoses/2.37 mm 2, brain invasion or at least three of the following criteria: sheeting architecture, hypercellularity, small cells, macronucleoli, necrosis; Grade III tumour, with ≥20 mitoses/2.37 mm 2 or anaplasia. Slides with grading disagreement were reviewed to define a consensus diagnosis and to assess reproducible criteria. Concordance between histologic grade and the consensus diagnosis, as well as intra‐ and inter‐observer agreements for each criterion, were statistically analysed. Concordance between histologic grade and consensus diagnosis ranged from 59% to 100%, with lower concordance for Grade I and II tumours. The lowest inter‐observer agreement was recorded for macronucleoli, small cells, hypercellularity and sheeting architecture. Tumour invasion and necrosis displayed fair agreement, while moderate agreement was reached for mitotic grade and anaplasia. The following recommendations were issued to improve the reproducibility of canine meningioma grading: (1) Assess mitotic grade in consecutive HPFs within the most mitotically active area; (2) Define invasion as neoplastic protrusions within central nervous tissue without pial lining; (3) Report spontaneous necrosis; (4) Report prominent nucleoli when visible at ×100; (5) Report pattern loss when visible at ×100 in >50% of the tumour; (6) Report necrosis, small cells, hypercellularity and macronucleoli, even when focal; (7) Report anaplasia if multifocal.